Loss-chasing, alexithymia, and impulsivity in a gambling task: alexithymia as a precursor to loss-chasing behavior when gambling - Bibby, Peter A. (Frontiers Media, 2016)
Objective: To examine the relationship between loss-chasing, the propensity to continue gambling to recover from losses, alexithymia, a personality trait associated poor emotional processing and impulsivity, the tendency to act quickly without reflection or consideration of the consequences.